تكنولوجيا المعلومات و دوره في تحسين عملية التدقيق التشغيلي - مارف, كمال رؤف (Sulaimani Journal for Humanities, 2021)
The development witnessed by the world included all fields, including the field of information technology, and considering this technology one of the influencing and important variables in all sectors, including the government sector and its components of functions and tasks, and that the function of internal auditing in general and operational audit, in particular, was among the jobs affected by this modern technology. The auditors and those in charge of managing these institutions benefited from it in carrying out their work and duties and thus achieving the goals of the institutions efficiently, effectively, and economically, and this study came to shed light on the role of information technology in improving the process of operational auditing in the government sector, through a study A case of one of the departments belonging to this sector (Bashamakh Customs Directorate of the Ministry of Finance and Economy in the Kurdistan Regional Government of Iraq), in which the method of work was changed from the manual system to the electronic system in 2017. The study reached a set of conclusions, the most important of which was the effective role of information technology in improving the process of operational auditing and thus achieving the objectives set for the directorate represented in increasing revenues through tax collection, improving the quality of services provided, making the audit process more accurate, fast and efficient, as well as assistance. In achieving compliance and compliance with legislation and laws. The researcher recommended a set of recommendations to improve operational processes, some of which are at the core of the operational audit process, which is to benefit from the human and material capabilities of the directorate to maximize revenues as well as strengthen the internal control system. And the need to pay attention to the issue of customs exemptions and how to deal with imports and exports of goods.